Progress of ITER-India activities for ITER deliverables—challenges and mitigation measures. (18th October 2019) - Chakraborty, A.K.; Baruah, Ujjwal; Mukherjee, Aparajita; Rao, S.L.; Kumar, Vinay; Singh, Narinder P.; Kumar, Ajith; Gupta, Girish; Vaghela, Hitensinh; Pathak, H.A.; Pandya, Hitesh; Padasalagi, Shrishail; et al.
Abstract: The responsibilities of ITER-India include a mix of precision, heavy, R&D intensive and interface intensive systems, under the built-to-print and functional systems categories. In several systems, the components are the first or largest of their kind. The uniqueness of component specifications and adherence to the desired quality standards considering the harsh nuclear environment in which the components need to operate and survive the lifetime of ITER leads to a challenging situation—namely that neither the existing laboratories nor potential suppliers have ever done or encountered such a scale-up (either in size, capacity, precision, quality etc) and in many cases do not have even the research and development (R&D) infrastructure to match ITER's requirements. To bridge this gap, ITER-India adopted a two-step approach of first manufacturing prototypes as per ITER-specific standards and then subjecting them all to critical evaluation before launching bulk production. Some of the key areas of development include demonstrations of the following: (a) 1.5 MW radiofrequency power in the 35–65 MHz frequency range under Diacrode and Tetrode tube technologies for the ion cyclotron resonance heating system; (b) a low loss multi-process pipe cryogenic transfer line and the development of a 3.3 kg s −1 cold circulator for the cryoline and cryo-distribution system; (c) an angled accelerator grid with precision in positioning of apertures within 50 μ m, as a first of its kind development, and special, ITER grade, copper alloy development for the diagnostic neutral beam (DNB) system. Full scale test facilities have been built for the performance assessment of the DNB, the electron cyclotron and ion cyclotron sources, cryogenic transfer lines and diagnostics systems. A summary is presented of the technical features of the major areas of procurements, notable achievements in R&D and manufacturing and their application in the Indian R&D related to fusion.